A Study of Irrigation Performance Index and Real Cost Value of Irrigation Operations and Maintenance in Surak Irrigation Area - Prayogo, Tri Budi; Wahyuni, Sri; Iqbal, Muhammad (Fakultas Teknik UB, 2021)
Irrigation Asset Management is required to maintain the value of irrigation asset function and condition. Surak Irrigation Area is located in Lawang Sub-District, Malang Regency. After resurveying in 2020, 21 points of damage were found in Surak Irrigation Area. Irrigation performance index was found to be 77.56% (moderate condition) for which the physical infrastructure aspect is 39.1%, the water availability aspect is 5.4%, the planting index aspect is 4.4%, the supporting facilities for operation and management aspect is 7.8%, the organizational and personnel aspect is 10.8%, the documentation aspect is 3.8%, and the Water User Association aspect is 6.3%. Priority calculation utilized the ranking method, which ranks asset values from the lowest to the highest. The result was that 24 assets are in moderate condition, 43 assets are in good condition, and 146 are in very good condition. The real cost value of irrigation operations and maintenance was calculated to be IDR 1,561,741,648, with IDR 208,506,890 for operating costs and IDR 1,353,234,758 for maintenance costs. For rehabilitation, it was found that 24 assets need regular maintenance and repair, 24 assets need regular maintenance, and 146 assets need routine maintenance